Agricultural development based on application of biological high techs in China and lessons and suggestions for Vietnam - Khuong, Le Tat; Hung, Ta The; Tuan, Tran Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
During more than two decades of application of policies for bio-technological development, China has used and exploited successfully achievements of high techs in this new scientific field and China has become one of the leading countries in fields of development of bio-technologies. These achievements are fruits of policies applied by the Chinese Government for development of high techs based agriculture including the improvement of research system as well as institutional mechanisms to encourage the development of bio-technologies for commercialization ends. It is possible to see the development policies for high techs based agriculture in China is close to the one which are being formed and developed in Vietnam. Experience in organization, administration and coordination between ministries/branches as well as involvement of enterprises in China are good lessons for forming, propagating and developing bio-technologies in Vietnam in the coming time. Code: 13041001